Youth Perception of QS. Al Alaq Verse 1-5 Relationship with Interest in Learning the Qur'an - Sa’idah, Susan (Interdisciplinary Social Studies, 2021)
Many adults do not want to care and understand them, or they have their own world that is difficult for parents to touch. Based on the phenomenon, researchers are interested in further researching what causes Muslim teenagers to be less attentive and less interested in learning the Qur'an. This study aims to determine the Perception of Adolescents towards the Qur'an Surat Al-Alaq verses 1-5 and its Relationship with Their Interest in Learning to Read and Write the Qur'an in Cibiuk Kidul Village, Cibiuk District, Kabupaaten Garut). This study used a qualitative approach. The method used was descriptive. The data collection implemented was library research. The data collection method uses descriptive methods and the author performed content analysis. Based on the correlation between variable X (Adolescent Perceptions of the Qur'an Surat Al-Alaq verses 1-5) and variable Y (Their Interest in Learning to Read and Write the Qur'an) a correlation coefficient of 0.95 with a very high qualification was obtained. This proves that the positive relationship of Adolescent Perceptions of the Qur'an Surat Al-Alaq verses 1-5 and its Relationship with Their Interest in Learning to Read and Write the Qur'an in Cibiuk Kidul Village, Cibiuk District, Kabupaaten Garut is very high.